2018
DOI: 10.1136/oemed-2017-104619
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and educational inequalities in exit from employment at older ages: evidence from seven prospective cohorts

Abstract: ObjectivesPast studies have identified socioeconomic inequalities in the timing and route of labour market exit at older ages. However, few studies have compared these trends cross-nationally and existing evidence focuses on specific institutional outcomes (such as disability pension and sickness absence) in Nordic countries. We examined differences by education level and occupational grade in the risks of work exit and health-related work exit.MethodsProspective longitudinal data were drawn from seven studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 36 publications
(39 reference statements)
4
88
0
Order By: Relevance
“…The HRs for DBs were highest among the blue-collar employees in the present study. This is in line with a previous study, in which the data were drawn from seven independent studies in Finland, France, the UK and the USA, and which reported an association with a low occupational grade and increased risks of health-related exit from work (Carr et al 2018). A Finnish cohort study found that higher occupational classes are two times more likely to continue working beyond retirement age than lower occupational classes, while another cohort study found that hospitalization was slightly more associated with increased DB in the lower occupational classes.…”
Section: Discussionsupporting
confidence: 93%
“…The HRs for DBs were highest among the blue-collar employees in the present study. This is in line with a previous study, in which the data were drawn from seven independent studies in Finland, France, the UK and the USA, and which reported an association with a low occupational grade and increased risks of health-related exit from work (Carr et al 2018). A Finnish cohort study found that higher occupational classes are two times more likely to continue working beyond retirement age than lower occupational classes, while another cohort study found that hospitalization was slightly more associated with increased DB in the lower occupational classes.…”
Section: Discussionsupporting
confidence: 93%
“…A recently published study showed that persons with a lower socioeconomic position were more likely to exit paid employment into disability benefits (6). However, educational inequalities in exit from paid employment can be the result of a higher prevalence of poor health among lower-educated workers or a stronger association between poor health and exit from paid employment.…”
Section: Schuring Et Almentioning
confidence: 99%
“…A recent study using longitudinal data from seven cohort studies in Finland, France, the UK, and the USA provided evidence for socioeconomic inequalities in the risk of health-related exit from paid employment among older workers (6). Low education was associated with an increased risk of leaving paid employment for health reasons in six out of seven cohort studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, compared with lower educated workers, higher educated workers tend to have lower physical work demands, 22 a stronger attachment to work, 23…”
Section: Introductionmentioning
confidence: 99%